2008
DOI: 10.1159/000165352
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Gut Hormones with Irritable Bowel Syndrome

Abstract: Background: Irritable bowel syndrome (IBS) is a functional bowel disorder which is characterized by abdominal pain and disturbed bowel habits. The pathophysiological mechanism is complex and still remains incompletely clear. Alterations at both the central and the peripheral level are thought to contribute to the symptoms of IBS, including psychosocial factors, visceral hypersensitivity and abnormal gastrointestinal motility and secretion. Several gut peptides contribute to the regulation of gastrointestinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Our group previously showed that MCs and VIP regulate the ileal barrier of healthy humans and during stress in rats via VIP-receptors (VPAC1/VPAC2) on MCs 25 . Increased plasma levels of VIP have been reported in IBS patients 31 and in an IBS-animal model 32 , and there appears to be a positive correlation between an increased intestinal transcellular permeability and amount of mucosal MCs in IBS-D 33 . In addition, increased MC numbers and tryptase levels have been found in biopsies of caecum 34 and jejunum 35 of IBS patients, and increased paracellular permeability and higher MC numbers were demonstrated in colon of IBS-D patients 18 .…”
Section: Introductionmentioning
confidence: 94%
“…Our group previously showed that MCs and VIP regulate the ileal barrier of healthy humans and during stress in rats via VIP-receptors (VPAC1/VPAC2) on MCs 25 . Increased plasma levels of VIP have been reported in IBS patients 31 and in an IBS-animal model 32 , and there appears to be a positive correlation between an increased intestinal transcellular permeability and amount of mucosal MCs in IBS-D 33 . In addition, increased MC numbers and tryptase levels have been found in biopsies of caecum 34 and jejunum 35 of IBS patients, and increased paracellular permeability and higher MC numbers were demonstrated in colon of IBS-D patients 18 .…”
Section: Introductionmentioning
confidence: 94%
“…Several of these molecules have been found to associate with functional gastrointestinal disorders and their symptoms such as IBS and functional dyspepsia. [6][7][8] These cells interact and integrate with the enteric nervous system, a complex network of neurons and glia distributed throughout the gut wall, which regulates most aspects of intestinal functions. 9 Recently, it has been shown that different cell types underneath the intestinal epithelial layer, such as stromal cells, immune cells, and enteric glia, provide important signals involved in regulating intestinal epithelial homeostasis/repair and modulating sensitivity of the enteric nervous system.…”
Section: Different Functions Of Intestinal Cell Typesmentioning
confidence: 99%
“…The most frequently addressed peptides include 5-hydroxytyptamine (5-HT), cholecystokinin, glucagon-like peptide, somatostatin, neuropeptide Y, endocannabinoid, vasoactive intestinal polypeptide, corticotropin releasing hormone (CRH), etc. [1,7,23,41,46,[69][70][71][72] . For example, the fact that 5-HT related agonists and antagonists have been developed effectively to treat either IBS-C or IBS-D patients strongly suggests that certain peptide dysfunction is one of important mechanisms leading to IBS [1,7,23] .…”
Section: Visceral Hypersensitivitymentioning
confidence: 99%